(untitled) (Revista científica Olimpia, 2020)
Weightlifting, sport emerged in the XIX century from one of the natural activities that the men most realize from remote times: the lift and transport of different loads, is, at present, an inclusive sport for both sexes, with potentiality to sum a substantial number of medals in multisport events at different levels. In Cuba, his practice begins from early ages (11-12 years) until arrive at high performance in junior and adults categories. Nevertheless been a sport that had attributed negative effects, is one of the physical exercises with lesser incidence of lesions. The investigation had as objective to identify the more frequent lesions in a sample of different categories Cuban weightlifters (n = 88), as just as the factors that predisposed and to propose some rules for his prevention.